Language Policy in Post-Soviet Latvia - Chao Liu; Chao Sun (Вестник Кемеровского государственного университета. Серия: политические, социологические и экономические науки)
Since the collapse of the Soviet Union, the Republic of Latvia has been altering its language policy towards the Russian language as a language of national minority. The article describes the evolution of language-related laws, as well as the social and role of the Russian language in Latvia. The authors combined various methods of linguistics, history, and politics to establish the importance of the Russian language in Latvian education and socio-cultural life. The current language policy focuses on consolidation, self-identity, and historical memory of the Latvian population. The resulting social tension requires more diversity and inclusivity to maintain the balance between the languages and preserve the cultural heritage. Stronger language rights for ethnic minorities could improve the social development and unity of Latvia. Latvia’s experience is important for China as a multinational country as it strives to find a balance between promoting the state language and protecting the languages of national minorities. The study of Latvia’s modern language policy and its historical roots contributes to the mutual cooperation between Latvia and China in economics, education, and culture. A good understanding of the national language is a key factor for business communications and cultural exchange.